Co-Parenting Patterns in Post-Divorce Child Education: A Systematic Literature Review Based on Islamic Values - Rini Novianti Yusuf; Kartimi Kartimi; Iman Subasman; Abdul Karim; Hamadah Azzam; Nur Muhammad Iskandar (Jurnal Pendidikan Terapan, 2026)
Purpose: This study aims to analyze co-parenting patterns in post-divorce child education and to examine the integration of Islamic values in parenting practices, particularly in response to the increasing divorce rate in Indonesia and its impact on children’s emotional, social, and academic development. Method: This research employs a Systematic Literature Review (SLR) approach using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Data were collected from Google Scholar and Scopus databases, focusing on publications from 2010 to 2025. A total of 124 articles were initially identified, with 36 articles meeting the inclusion criteria and analyzed using content analysis techniques. Findings: The findings indicate that co-parenting patterns in post-divorce families can be classified into three main types: cooperative, parallel, and high-conflict. Cooperative co-parenting is associated with positive outcomes in children’s well-being and academic achievement, while high-conflict co-parenting increases the risk of behavioral problems. Furthermore, the effectiveness of co-parenting is influenced by communication quality, clarity of role distribution, and conflict management skills. In the context of Muslim families, Islamic values such as shura (consultation), amanah (responsibility), ‘adl (justice), and ta’awun (cooperation) play a significant role in strengthening constructive co-parenting practices. Research Implication: This study emphasizes the importance of integrating Islamic values into co-parenting practices as a strategic approach to support children’s holistic development in post-divorce families. It also provides a conceptual basis for educators and parents to develop more adaptive and value-based parenting strategies. Originality: This research offers a conceptual framework of Islamic values-based co-parenting that bridges contemporary parenting models with Islamic principles, providing a contextual and practical contribution to post-divorce child education.